Zweidimensionierte Alltäglichkeit und Fürsorgeanalyse bei Heidegger in den 1920er Jahren - Ivanoff-Sabogal, Christian (Bollettino Filosofico, 2020)
Both the early hermeneutics of facticity and the mature question of being have their starting point in the investigation of everyday life. Underlining Being and Time, we discuss two dimensions of the everyday life phenomenon, namely its «content» and «modal» sense. The relationship between both of them shows up as a dynamic tendency and an internal reference. On the basis of the distinction of the two-dimensional everyday life we deal with the problem of modal indifference, which is apparently closely connected with the «content» sense of everyday life, in order to find out whether it could be a third way to execute existence besides authenticity and inauthenticity. We reject the plain correspondence between everyday life with modal indifference and inauthenticity, taking into account the thesis in Being and Time about the possibility of authentic liberating solicitude in the facticity of being together, whose analysis remains within the limits of everyday life. Keywords: Authenticity, Everyday Life, Modal Indifference, Ontology, Solicitude